Shaping Customer Satisfaction in Online Food Delivery: The Roles of Service Quality, Perceived Value, and Trust in Indonesia - Nadya Carissa Fernanda Putri; Nabila Kharimah Vedy (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effects of service quality, customer perceived value, and trust on customer satisfaction, while also analyzing the meditating role of trust. Consumer shopping behavior has shifted alongside the growth of internet usage, leading to the rapid development of online food delivery (OFD) services. Online food delivery enables customers to conveniently order meals online and receive delivery directly to their address. In this highly competitive business environment, understanding the determinants of customer satisfaction is crucial. This study aims to examine service quality, customer perceived value, and trust in relation to customer satisfaction, both directly and to investigate the role of trust as a mediator. A quantitative research design was adopted and analyzed using PLS-SEM with the SmartPLS software. Data were collected through an online survey of 175 ShopeeFood users. The results reveal that service quality, customer perceived value, and trust significantly and positively influence customer satisfaction. Furthermore, trust is confirmed as a significant mediator in the relationship between service quality and customer perceived value toward customer satisfaction.